Introduction: Parties at the Grassroots: Local Party Branches in the Low Countries - Wauters, Bram; Otjes, Simon; van Haute, Emilie (Politics of the Low Countries, 2020)
Local party branches are the basic organisational unit of political parties. They serve specific functions for parties (Clark, 2004; Geser, 1999; Paulis, 2017; Roscoe & Jenkins, 2015). They are recruiting and training agencies of party members, activists and political personnel. More broadly, they function as a learning environment for citizens to get familiar with political issues. They facilitate membership recruitment and integration (Carty & Eagles, 2005; Pruysers, 2018). They are the door to the national party (Selle & Svasand, 1983). Most often, they designate representatives of the local branch to the higher party levels and are involved in selecting candidates for local elections. They provide a level to experiment with party renewal, as it is easier for a party to test new strategies at the local level, where changes are less visible and where their impact is less far-reaching. Furthermore, local branches provide participatory incentives for party members and interested citizens, be it in the form of social activities (such as dinners) or political activities (such as debates) (André & Depauw, 2016). These activities favour internal socialisation to the party, and, indirectly, party cohesion. Local branches also provide human resources to the party in the form of volunteer work during electoral campaigns (Van Aelst, Van Holsteyn & Koole, 2012; Webb, Poletti & Bale, 2017). Finally, local branches are information and communication channels between the higher party levels and the grassroots.